Revolusi Mental Generasi Muda Indonesia Guna Menyiapkan Golden Age 2045 Dalam Telaah Al-Qur’an Surah Al-Ra’d Ayat 11: Studi Kajian Tafsir Tematik - Moh. Mauluddin, Ahmad Ilham Wahyudi, Sabila Rafiqah Fitriani (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
Indonesia is currently being hit by a multi-dimensional crisis from all aspects of life and has become an easy field for spreaders of moral viruses, including criminal acts, drugs, pornography, and value-free media. Of the various kinds of problems, mental revolution is realy urgent in welcoming the golden age of 2045 which is strongly influenced by the mentality of the contemporary young generation who are more familiarly called the millennial generation. Therefore, the perfection of the instructions of the Qur'an becomes a reference to be used as a solution in every dynamic of human problems, including in terms of mental revolution. In this study, the Al-Qur'an Surah Ar-Ra'du Verse 11 is used as a model in the application of mental revolution.